Early Weaning Increases Diarrhea Morbidity and Mortality Among Uninfected Children Born to HIV-infected Mothers in Zambia - Fawzy, Ashraf (Oxford University Press, 2011)
Background. Early weaning may reduce human immunodeficiency virus (HIV) transmission but may have deleterious consequences for uninfected children. Here we evaluate effects of early weaning on diarrhea morbidity and mortality of uninfected children born to HIV-infected mothers. Methods. HIV-infected women in Lusaka, Zambia, were randomly assigned to breastfeeding for 4 months only or to continue breastfeeding until the mother decided to stop. Replacement and complementary foods were provided and all women were counseled around feeding and hygiene. Diarrhea morbidity and mortality were assessed in 618 HIV-uninfected singletons alive and still breastfeeding at 4 months. Intent-to-treat analyses and comparisons based on actual feeding practices were conducted using regression methods. Results. Between 4 and 6 months, diarrheal episodes were 1.8-fold (95% confidence interval (CI), 1.3–2.4) higher in the short compared with long breastfeeding group. Associations were stronger based on actual feeding practices and persisted after adjustment for confounding. At older ages, only more severe outcomes, including diarrhea-related hospitalization or death (relative hazard [RH], 3.2, 95% CI, 2.1–5.1 increase 4–24 months), were increased among weaned children. Conclusions. Continued breastfeeding is associated with reduced risk of diarrhea-related morbidity and mortality among uninfected children born to HIV-infected mothers in this low-resource setting despite provision of replacement and complementary food and counseling.  Clinical Trials Registration. NCT00310726.